Case Report: Pulmonary Metastases From Epithelioid Sarcoma in Extremity Favourably Responding to Immunotherapy With Camrelizumab - Gong, Tao-Jun; Tang, Fan; Zheng, Chuan-Xi; Wang, Jie; Wang, Yi-Tian; Zhang, Ya-Han; Luo, Yi; Zhou, Yong; Min, Li; Tu, Chong-Qi (Frontiers in Oncology, 2021)
Epithelioid sarcoma (ES) is a rare soft tissue sarcoma (STS), with limited therapies available for metastatic disease. Here, we describe a case of a 30-year-old male with ES of the left knee and underwent surgery and radiation therapy for the primary disease. After 2 years, he had local recurrence and underwent extensive resection surgery; however, adjuvant chemotherapies were delayed due to recurrent wound infection. Nine months after the second surgery, progressive disease was confirmed after detection of metastases to the lungs and inguinal lymph nodes. Amputation was performed for the local recurrence, followed by inguinal lymph nodes dissection. Pazopanib was transiently administered but discontinued as a result of wound dehiscence. The tumour specimens were detected with unexpected high level of PD-L1 expression and tumoural infiltrating lymphocytes. Subsequently, he received camrelizumab 2.0 mg/kg every 21 days for 18 cycles with rapid remission of the pulmonary metastases. This promising response to camrelizumab indicates that immunotherapies may be an alternative choice for patients with metastatic ES in lung based on analysing the tumour immune microenvironment.